2021
DOI: 10.3389/fphar.2021.763163
|View full text |Cite
|
Sign up to set email alerts
|

Si-Miao-Yong-An Decoction for Diabetic Retinopathy: A Combined Network Pharmacological and In Vivo Approach

Abstract: Si-Miao-Yong-An decoction (SMYAD), a traditional Chinese medicine formula, is mainly used to clear away heat and detoxify and to promote blood circulation and relieve pain. Diabetic retinopathy (DR) is the most common type of microvascular complication caused by diabetes. This study is designed to examine the protective effect of SMYAD against DR and further to reveal the engaged mechanism via integrating network pharmacology and in vivo experimental evidence. Streptozotocin (STZ) was intraperitoneally injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Since its onset occurs after many years of diabetes progression, there is an opportunity to take steps to prevent vision loss ( 23 ). Therefore, drugs that inhibit retinal vascular endothelial cell proliferation are expectedly used to prevent further deterioration of DR. PDR is closely associated with the formation of acellular capillaries, which is obviously promoted by VEGF ( 24 , 25 ). Additionally, hyperglycemia also impairs the expression of tight-junction protein zonula occludens-1 (ZO-1) in the retina, which will increase the permeability of retinal capillaries, leading to blood extravasation and deterioration of DR ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its onset occurs after many years of diabetes progression, there is an opportunity to take steps to prevent vision loss ( 23 ). Therefore, drugs that inhibit retinal vascular endothelial cell proliferation are expectedly used to prevent further deterioration of DR. PDR is closely associated with the formation of acellular capillaries, which is obviously promoted by VEGF ( 24 , 25 ). Additionally, hyperglycemia also impairs the expression of tight-junction protein zonula occludens-1 (ZO-1) in the retina, which will increase the permeability of retinal capillaries, leading to blood extravasation and deterioration of DR ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human retinal capillary endothelial cells cultured in NG and HG were, respectively, seeded into 96-well plates (5 × 10 3 cells/well), incubated at 37 • C and 5% CO 2 for 24 h. The supernatant was discarded, and then the corresponding medium and different concentrations of BJ (10,25,50, 100, and 150 µg/mL) were added. After treatment with BJ for 24 h or 48 h, the supernatant was discarded, 100 µL of 10% CCK8 was added and incubated at 37 • C for 30 min, and the absorbance was measured at 450 nm using a microplate reader.…”
Section: Cell-counting Kit-8 Assaymentioning
confidence: 99%
“…It has been reported that retinal microglia under physiological conditions reside in the inner and outer plexiform layers, but STZ-induced diabetes promotes microglial migration into the neuronal or photoreceptor layers [52]. Both mRNA and protein levels of Iba1 are increased in retinal microglia from diabetic mice [21,24,25,[102][103][104][105][106][107] and rats [25,38,[108][109][110][111][112][113][114][115][116][117]. Not only microglia numbers but also retinal microglia morphology is affected, showing fewer branches as well as fewer and shorter processes [117,118], while endpoints are reduced and the number of microglia in contact with acellular capillaries increases [117].…”
Section: Streptozotocin (Stz)-induced Diabetic Micementioning
confidence: 99%
“…To clarify the functional interactions among the screened potential proteins, they were all imported to the String database (https://string-db.org/) to construct Protein-Protein Interaction (PPI) network (31). Then the PPI network was inputted into Cytoscape 3.8 software, and key proteins were identified by CytoNCA software according to betweenness centrality (BC), closeness centrality (CC), degree centrality (DC), Eigenvector centrality (EC), local average connectivitybased method (LAC), and network centrality (NC), which were greater than or equal to the median value (32).…”
Section: Protein-protein Interaction Networkmentioning
confidence: 99%